"They're Not Monsters!" Changing University Students' Perceptions of Child Sex Offenders through Education and Contact. Issue 2 (21st May 2021) - Wurtele, Sandy K.
Abstract: Child sexual abuse (CSA) is a global public health problem. Assessing public attitudes toward child sex offenders is important since public opinions have affected judicial decision-making regarding sex offender management policies and laws. Study objectives were to assess university students' perceptions of offenders before and after a Sex Crimes Against Children course, and examine the potential anti-stigmatizing effect of interacting directly with people who had committed sex crimes. Compared with a previous study where only indirect contact was available, students who had direct contact with offenders reported more positive affective responses, had more positive attitudes toward sex offender treatment and rehabilitation, along with lower support for post-sentencing policies. Findings support the humanizing impact of interacting with members of the stigmatized group. Better informed public opinion is essential to support evidence-based crime prevention policies and ultimately prevent CSA.